2013
DOI: 10.1002/pd.4205
|View full text |Cite
|
Sign up to set email alerts
|

The frontal space measurement in euploid and aneuploid pregnancies at 11–13 weeks' gestation

Abstract: First trimester FS measurement may improve first trimester combined screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…The measurement of PFSR proved to be challenging: incorrect placement of the MM line of only a few tenths of a millimeter has a large impact on the measured angle and consequently on the measurement of d2. In spite of a recent adaptation of the PFSR to facilitate its measurement in the first trimester, its detection rate for trisomies remained still about half of that in the second and third trimesters [18].…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of PFSR proved to be challenging: incorrect placement of the MM line of only a few tenths of a millimeter has a large impact on the measured angle and consequently on the measurement of d2. In spite of a recent adaptation of the PFSR to facilitate its measurement in the first trimester, its detection rate for trisomies remained still about half of that in the second and third trimesters [18].…”
Section: Discussionmentioning
confidence: 99%
“…Yazdi et al found that the MML coursed behind the prenasal skin in a considerable number of Down syndrome cases which is potentially predictive of fetal aneuploidy in the second and third trimester [20]. Recently, the same group reported significant differences between euploid and aneuploid fetuses (including trisomy 21, 18 and 13) regarding the frontal space assessed at 11-13 gestational weeks and the impact on first-trimester combined aneuploidy screening [23]. In contrast to the described MMN angle having its vertex on the anterior edge of the mandible, the previously described MNM (between 2 lines originating from the nasion and tracing the anterior borders of the mandible and the maxilla, respectively) [24] is found to be a weak DS marker as less than 25 % of trisomy 21 fetuses had abnormal values [22].…”
mentioning
confidence: 99%
“…Bakker et al berichteten, dass die pränasale Dicke bei etwa einem Drittel der aneuploiden Feten über der 97,5ten Perzentile liegt [50]. Die "prefrontal space ratio" aus dem zweiten Trimenon wurde etwas vereinfacht als "prefrontal space distance" untersucht [53]. Dabei wird eine Linie tangential von dem ventralsten Verknöcherungspunkt der Mandibula zur Maxilla gezogen und zur Stirn verlängert (▶ Abb.…”
Section: Auffälligkeiten Im Bereich Des Mittelgesichtsunclassified